The Roles of Smart Fertigation in Chili Farming - Tinaprilla, Netti; Muflikh, Yanti Nuraeni; Yanuar, Rahmat; Permata, Kurnia Intan (Jurnal Manajemen dan Agribisnis, 2024)
Smart farming technology has been developed with Agriculture 4.0 to improve productivity and yield quality and solve challenges such as climate change, labor shortage due to regeneration difficulties, and resource efficiency. The objectives of this study were to analyze (1) the characteristics of farmers and chili production using smart fertigation and (2) the cost structure, revenue, profit, and efficiency. The study used primary data from interviews with 83 farmers in Central and East Java. Analytical methods included descriptive statistics, Cobb-Douglas production functions, and R/C. The results showed that smart fertigation farmers, who represented 2% of the total, had higher education (17 years), longer training (124 days), and significant participation in farmer groups (100%). The role of smart fertigation in chili production is to increase productivity (from 8.35 t/ha to 20.67 t/ha), reduce fertilizer use (from 26.730 t/ha to 8.540 t/ha) and reduce labor requirements from 748.17 HOK/ha to 609.33 HOK/ha. Despite the higher farm costs/ha with smart fertigation, the higher total revenue (due to increased productivity and selling price) results in higher profit and efficiency (R/C). Keywords: smart fertigation, chili farming, adoption decisions, cost savings